PTEN Methylation Promotes Inflammation and Activation of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis - Li, Xiao-Feng; Wu, Sha; Yan, Qi; Wu, Yuan-Yuan; Chen, He; Yin, Su-Qin; Chen, Xin; Wang, Hua; Li, Jun (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is characterized by a tumor-like expansion of the synovium and subsequent destruction of adjacent articular cartilage and bone. In our previous work we showed that phosphatase and tension homolog deleted on chromosome 10 (PTEN) contributes to the activation of fibroblast-like synoviocytes (FLS) in adjuvant-induced arthritis (AIA), but the underlying mechanism is not unknown. In this study, we show that PTEN is downregulated while DNA methyltransferase (DNMT)1 is upregulated in FLS from RA patients and a rat model of AIA. DNA methylation of PTEN was increased by administration of tumor necrosis factor (TNF)-α in FLS of RA patients, as determined by chromatin immunoprecipitation and methylation-specific PCR. Treatment with the methylation inhibitor 5-azacytidine suppressed cytokine and chemokine release and FLS activation in vitro and alleviated paw swelling in vivo. PTEN overexpression reduced inflammation and activation of FLS via protein kinase B (AKT) signaling in RA, and intra-articular injection of PTEN-expressing adenovirus into the knee of AIA rats markedly reduced inflammation and paw swelling. Thus, PTEN methylation promotes the inflammation and activation of FLS in the pathogenesis of RA. These findings provide insight into the molecular basis of articular cartilage destruction in RA, and indicate that therapeutic strategies that prevent PTEN methylation may an effective treatment.